Tragic Heroines in Ancient Greek Drama - Roizman, Ḥanah (Bloomsbury Publishing Plc, 2021)
Cover page -- Halftitle page -- Series page -- Title page -- Copyright page -- Dedication -- CONTENTS -- ACKNOWLEDGMENTS -- Map -- ALPHABETICAL LIST OF DISCUSSED TRAGEDIES -- INTRODUCTION -- Pervasive Themes -- Themes Relating to the Characters -- Aristotle's Theory of Character -- The Eleven Heroines -- Translations -- CHAPTER 1 CLYTEMNESTRA -- CLYTEMNESTRA IN AESCHYLUS' AGAMEMNON -- The Ascendancy of Clytemnestra: Before Meeting Cassandra -- CLYTEMNESTRA IN LIBATION BEARERS AND EUMENIDES -- CLYTEMNESTRA IN SOPHOCLES' ELECTRA -- CLYTEMNESTRA IN EURIPIDES' ELECTRA -- CLYTEMNESTRA IN EURIPIDES' IPHIGENIA AT AULIS -- Conclusion -- DISCUSSION TOPICS -- CHAPTER 2 ELECTRA -- Introduction -- ELECTRA IN AESCHYLUS' LIBATION BEARERS -- ELECTRA IN SOPHOCLES' ELECTRA -- Confrontation with the Chorus -- Confrontation with Chrysothemis -- Confrontation with Clytemnestra -- Reunion with Orestes -- Electra and the Act of Revenge -- ELECTRA IN EURIPIDES' ELECTRA -- Electra's State of Mind and Motives -- Orestes' Return, the Recognition Scene-and Planning a Matricide -- Volatile and Unrealistic or a Strategic Planner? -- The Mother-Daughter Relationship and Confrontation with Clytemnestra -- The Ending -- ELECTRA IN EURIPIDES' ORESTES -- Love, Hatred, and Bloodthirst -- Revenge and Gender -- Conclusion -- DISCUSSION TOPICS -- CHAPTER 3 IPHIGENIA -- IPHIGENIA IN IPHIGENIA AMONG THE TAURIANS -- Introduction -- Iphigenia's Entrance -- Address to her Heart -- Iphigenia with Orestes and Pylades -- Iphigenia's Initiatives -- The Recognition -- IPHIGENIA IN IPHIGENIA AT AULIS -- Introduction -- Iphigenia -- Conclusion -- DISCUSSION TOPICS -- CHAPTER 4 ANTIGONE -- Introduction -- ANTIGONE IN SOPHOCLES' ANTIGONE -- Antigone's Intransigence -- Antigone's Single- Mindedness -- Antigone's Loyalties -- Antigone's Impulsiveness -- Antigone and Ismene -- Antigone and Creon.